DFT computation of quantum capacitance of pure and doped niobium nitrides for supercapacitor applications. Issue 13 (1st July 2021) - Bharti,; Ahmed, Gulzar; Kumar, Yogesh; Sharma, Shatendra
Abstract: The density of states and quantum capacitance of pure and doped niobium nitrides are investigated using density functional theory calculations. Out of pristine structures investigated, NbN is the most promising candidate for fabrication of supercapacitor electrodes with quantum capacitance values reaching up to 834.5 and 1683.7 Fg -1 at negative and positive electrodes respectively. These calculations are also performed for cobalt doped niobium nitrides. The results suggest that doping of niobium nitrides with cobalt can further increase the quantum capacitance significantly. Quantum capacitance of both pristine and doped niobium nitrides is found to be much higher than that of graphene near fermi level, thus suggesting that these structures can be preferred over graphene for supercapacitor electrodes. The temperature dependence of quantum capacitance is also investigated.